Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3897/jor.30.47778
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-borne vibration in Pacific field cricket courtship displays

Abstract: While thought to be widely used for animal communication, substrate-borne vibration is relatively unexplored compared to other modes of communication. Substrate-borne vibrations are important for mating decisions in many orthopteran species, yet substrate-borne vibration has not been documented in the Pacific field cricket Teleogryllus oceanicus. Male T. oceanicus use wing stridulation to produce airborne calling songs to attract females and courtship songs to entice females to mate. A new male morph has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…This lack of preference for specific purring variants suggests that directional selection by female choice is unlikely responsible for the population‐level differences in purring that we show here. In fact, our results may provide support for the ‘signal first’ hypothesis of divergence in animal communication where signals diverge first among groups, followed by the evolution of receiver preferences for these new signal characteristics and ultimately reproductive isolation (Bradbury & Vehrencamp, 2011; Broder, et al, 2021). If preferences for certain purring songs do subsequently develop in females at certain locations but not others, or differences in preferences evolve across populations, divergence among populations could accelerate.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This lack of preference for specific purring variants suggests that directional selection by female choice is unlikely responsible for the population‐level differences in purring that we show here. In fact, our results may provide support for the ‘signal first’ hypothesis of divergence in animal communication where signals diverge first among groups, followed by the evolution of receiver preferences for these new signal characteristics and ultimately reproductive isolation (Bradbury & Vehrencamp, 2011; Broder, et al, 2021). If preferences for certain purring songs do subsequently develop in females at certain locations but not others, or differences in preferences evolve across populations, divergence among populations could accelerate.…”
Section: Discussionsupporting
confidence: 67%
“…The residuals of the MANOVA were heavy‐tailed for songs and wings, potentially deviating from normality, so we confirmed results using a nonparametric permutational multivariate analysis of variance with the R package vegan (Oksanen et al, 2022). We included body size (measured as pronotum width; Moradian & Walker, 2008; Broder, et al, 2021; Tan, 2022) in our models because it can impact an individual's song and wing characteristics in some cricket species (Moradian & Walker, 2008; Tan, 2022; Whitman, 2008), and since the purring is generated using an altered instrument with novel wing‐song relationships (Gallagher et al, 2022), we wanted to be sure that any phenotypic differences we found among populations were not simply due to differences in body size. To determine whether there were morphological differences among populations in harp width we used a two‐way analysis of variance (ANOVA) with population, body size, and their interaction as independent variables.…”
Section: Methodsmentioning
confidence: 99%
“…This reveals the complexity and synchronisation between multiple signalling mechanisms, including a drumming signal that went completely unnoticed despite decades of study of this model species. Along with the recent discovery of drumming in the Paci c led cricket (Broder et al 2021), this calls for revisiting cricket courtship behaviour, with a speci c focus on vibrational signals that may complement stridulation.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, an investigation into the vibrational channel in the paci c eld cricket, Teleogryllus oceanicus, revealed a previously unknown drumming signal accompanying the song (Broder et al 2021). Yet, the signal's function remained unclear, as a follow up study showed female preference for nondrumming over drumming individuals (Wikle et al 2023).…”
Section: Introductionmentioning
confidence: 97%
“…Interestingly, recent evidence suggests that this retention of singing motor behaviour in silent crickets could facilitate evolutionary re‐emergence of the sexual signal, perhaps with different acoustic properties (Schneider et al ., 2018; Bailey, Pascoal & Montealegre, 2019). This might be expected in cases where benefits of mate attraction outweigh risks of attracting predators or parasites, or in which ‘clandestine’ communication is possible (Tinghitella et al ., 2018, 2021; Broder et al ., 2021b).…”
Section: Examples Of Vestigial Behaviours Across Contextsmentioning
confidence: 99%